2010
DOI: 10.1007/s10067-010-1618-9
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori seropositivity in fibromyalgia syndrome

Abstract: Although there are some studies suggesting relation between different types of infection and fibromyalgia syndrome (FM), there is presently no proof that FM is caused by an infection. Helicobacter pylori (HP) infection may cause extragastric manifestations. Inflammation is an important mediator of increased sympathetic nervous system activity and may lead to pain in fibromyalgia patients. In this study, we aimed to investigate the HP seropositivity in fibromyalgia patients compared with controls for possible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In addition, an increased prevalence of FMS has been found in patients with hepatitis B virus, hepatitis C virus, HIV, human T cell lymphotropic virus, and Mycoplasma infections [401][402][403]. Conversely, there are some reports of higher seropositivity rates for certain infectious agents in FMS patients compared to healthy controls [401,404]. It has long been held that Lyme disease increases the risk of FMS, but a recent study showed that the incidence of FMS in patients with cultureconfirmed Lyme disease did not exceed that of the general population during long-term follow-up [405].…”
Section: Cytokinesmentioning
confidence: 97%
“…In addition, an increased prevalence of FMS has been found in patients with hepatitis B virus, hepatitis C virus, HIV, human T cell lymphotropic virus, and Mycoplasma infections [401][402][403]. Conversely, there are some reports of higher seropositivity rates for certain infectious agents in FMS patients compared to healthy controls [401,404]. It has long been held that Lyme disease increases the risk of FMS, but a recent study showed that the incidence of FMS in patients with cultureconfirmed Lyme disease did not exceed that of the general population during long-term follow-up [405].…”
Section: Cytokinesmentioning
confidence: 97%
“…11,12 Studies focusing on extragastric manifestations of H. pylori infection such as sideropenic anemia and idiopathic thrombocytopenic purpura have been published, 5 however, literature regarding the effect of this microorganism on FMS is rather limited. 4 To date, only two studies investigated the possible association between H. pylori and FMS. In these studies, Malt et al 13 reported similar rates of H. pylori seropositivity in patients with FMS (n=28) and controls (n=39), while Akkaya et al 4 found that the prevalence of immunoglobulin (Ig) G anti-H. pylori antibodies was significantly higher in fibromyalgia patients (67.7%) compared to controls (43.9%).…”
Section: Discussionmentioning
confidence: 99%
“…4 To date, only two studies investigated the possible association between H. pylori and FMS. In these studies, Malt et al 13 reported similar rates of H. pylori seropositivity in patients with FMS (n=28) and controls (n=39), while Akkaya et al 4 found that the prevalence of immunoglobulin (Ig) G anti-H. pylori antibodies was significantly higher in fibromyalgia patients (67.7%) compared to controls (43.9%). However, among these patients, there were no significant differences in the clinical manifestations of FMS between H. pylori seropositive versus seronegative patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations